Causes and consequences of fever in Amazonian pregnant women: A large retrospective study from French Guiana. - Najeh Hcini; Véronique Lambert; Olivier Picone; Jean-Francois Carod; Mérédith Mathieu; Romane Cousin; Ferroudja Akli; Gabriel Carles; Célia Basurko; Léo Pomar; Loïc Epelboin; Mathieu Nacher (Public Library of Science (PLoS), 2023)
Objective The aim of this study was to describe different causes and consequences of fever during pregnancy in Western French Guiana and along the Maroni River. Study design A retrospective single-center study including all patients with a history of documented fever ≥ 38°C during pregnancy at the West French Guiana Hospital for 9 years. Postpartum fever and nosocomial infections were excluded. We focused on medical history and on clinical and biological findings. Causes were characterized as confirmed or uncertain and then classified as preventable or non-preventable. Results A total of 940 pregnant women who experienced at least one episode of fever were included and compared to 23,811 deliveries who occurred during the same period without documented fever. Among them, 43.7% (411/940) were in labor. About 3.7% (35/940) of febrile pregnant women had at least two episodes of fever, while 0.3% (3/940) had a coinfection at the time of diagnosis, resulting in a total of 978 febrile episodes. Among them, causes remained unknown or uncertain in 7.6% (75/978) and 0.9% (9/978) of cases, respectively. Among confirmed causes of fever throughout pregnancy (n = 483), the most common known cause was arbovirus infection (146/483, 30.2%), followed by urinary tract infection (134/483, 27.7%), chickenpox (27/483, 5.6%), and gastrointestinal (14/483, 2.9%) and pulmonary infections (10/483, 2%). Mothers with fever had a higher risk of cesarean section (19.8% vs 15.5%, aOR 1.3 [95% CI 1.14-1.6], stillbirth (5.5% versus 1.9%, aOR 2.7 [95% CI 2-3.7]), and preterm delivery < 34 weeks of gestation (7.2% vs 4.7%, aOR 1.5 [95% CI 1.2-2]. Conclusions In the Amazon region, causes of fever are diverse and often associated with epidemic waves, notably arboviruses. This must be considered when exploring possible causes of fever during pregnancy in these localities, including fetal anomalies and/or fetal loss. Physicians should consider the epidemiological context and avoid generalizations. Given the impact of emergent agents such as arboviruses on pregnancy, particular attention must be paid to the epidemiological context. This study can also help clinicians when managing fever in pregnant travelers or in their partner after having visited exposed areas. In this context, fetal abnormalities and adverse obstetric outcomes should be explored accordingly.